IWRM Discourses, Institutional Holy Grail and Water Justice in Nepal - Clement, Floriane; Suhardiman, Diana; Bharati, Luna (2017)
Integrated Water Resources Management (IWRM) still stands today as one of the most influential governance models in the water sector. Whereas previous analyses of IWRM have focused on the effectiveness of the institutional models it embodies and on policy implementation gaps, we examine the meanings that IWRM discourses have given to water management issues and how these meanings have in turn supported certain policy choices, institutions and practices. We use discourse analysis to study IWRM discourses in Nepal, where IWRM was introduced as the guiding policy principle for water management more than a decade ago, but not yet operationalised. We argue that IWRM discourses have operated a discursive closure in policy debates, thereby limiting the range of policy and institutional choices perceived as politically possible. In particular, we found that the promotion of IWRM as an institutional holy grail has obscured critical issues of social (in) justice related to water resources development by promoting an apolitical and techno-managerial vision of water development, largely centralised and relying on expert knowledge. We defend the need to move away from institutional panaceas and towards deliberative processes that allow alternative voices, discourses and knowledge.